CTXφ immunity: Application in the development of cholera vaccines - Kimsey, Harvey H. (The National Academy of Sciences, 1998)
CTXφ is a filamentous bacteriophage that encodes cholera toxin, the principal virulence factor of Vibrio cholerae. CTXφ is unusual among filamentous phages because it encodes a repressor and forms lysogens. CTXφ can infect the existing live-attenuated V. cholerae vaccine strains derived from either the El Tor or classical V. cholerae biotypes and result in vaccine reversion to toxinogenicity. Intraintestinal CTXφ transduction assays were used to demonstrate that El Tor biotype strains of V. cholerae are immune to infection with the El Tor-derived CTXφ, whereas classical strains are not. The El Tor CTXφ repressor, RstR, was sufficient to render classical strains immune to infection with the El Tor CTXφ. The DNA sequences of the classical and El Tor CTXφ repressors and their presumed cognate operators are highly diverged, whereas the sequences that surround this “immunity” region are nearly identical. Transcriptional fusion studies revealed that the El Tor RstR mediated repression of an El Tor rstA-lacZ fusion but did not repress a classical rstA-lacZ fusion. Likewise, the classical RstR only repressed a classical rstA-lacZ fusion. Thus, similar to the mechanistic basis for heteroimmunity among lambdoid phages, the specificity of CTXφ immunity is based on the divergence of the sequences of repressors and their operators. Expression of the El Tor rstR in either El Tor or classical live-attenuated V. cholerae vaccine strains effectively protected these vaccines from CTXφ infection. Introduction of rstR into V. cholerae vaccine strains should enhance their biosafety.